2015
DOI: 10.1007/s11071-015-2502-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction for breakup of spiral wave in a regular neuronal network

Abstract: Target wave and spiral wave can regulate the collective behaviors of electrical activities in neuronal systems as a powerful 'pacemaker'. Disordered states occur when normal signal propagation among neurons is disturbed and neuronal disease could be induced. In this paper, a stable rotating spiral wave is developed as initial state that the two-dimensional neuronal network of Hindmarsh-Rose neuron shows distinct periodicity and regularity in space, and then, some parameters are changed sharply to model the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 36 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…In addition, our future work will also include predicting power grid collapse through series analysis similar to the method presented in [60,61] such that effective measures can be taken in time to avoid system collapse.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our future work will also include predicting power grid collapse through series analysis similar to the method presented in [60,61] such that effective measures can be taken in time to avoid system collapse.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the wellknown neuron models, networks with different topological connections have been set to investigate the synchronization stability [36,37], pattern selection, and mode transition in collective behaviors [38][39][40][41][42][43][44][45]. Indeed, reliable and biophysical neuron model is critical and important for further investigation on neurodynamics and potential mechanism of some neuronal diseases [46].…”
Section: Complexitymentioning
confidence: 99%
“…Yamada and Kashimori [29] found that the learning of face stimuli makes the functional connections between these inferior temporal networks. Ma et al [30][31][32] investigated the death and breakup of spiral wave in the neuronal network. With the deepening of research development, more and more achievements are observed [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%